USE OF DOPAMINE ANTAGONISTS ON INDUCED SPAWNING OF INDIAN MAJOR CARPS - SINGH, KULDIP; DUTT, S.; ALI, M.; BISWAS, R. K. (Journal of Indian Fisheries Association, 2015)
To test the efficacy of the technique of using dopamine - antagonists with pituitary extracts, experi ents were conducted in July/August, 93, at the CIFE Fresh water Fish Farm, Powerkheda. In all, 35 sets (1 female x 2 male in each set) were tried individually. 19 sets were treated with Domperidone (DOM) and Carp Pituitary Extract (CPE) and they constituted the experimental sets, while the rest 16 were treated with CPE and formed the control sets. The breeding, complete ovulation and hatching was 84.2%, 87.5% and 85.7%, respectively in the experimental sets whereas it was 93. 7%, 60% and 72. 7%, respectively in case of control sets. Experimental sets yielded 1.20 lakh spawn/kg body wt. (female) as compared to 0.83 lakh spawn kg body wt. (female) received from control sets on average basis. When DOM was used @ 50-60% there was 100% breeding success but when increased to 70%, breeding rate fell to 66%. In mass breeding of Catla in the Circular hatchery DOM mixed with CPE in 50:50 ratio gave excellent results.